Discovery Learning dengan Geogebra untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis - Fauziah Hakim; Sitti Inaya Masrura; Gaffar Gaffar (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: The purpose of this research was to see how discovery learning with Geogebra can improve the ability to understand mathematical concepts. The research which was held in class XI Madrasah Aliyah Negeri Majene was a classroom action research conducted in 2 cycles. Data analyzed in the form of activity data or activities of teachers and students in carrying out discovery learning with Geogebra obtained through observation sheets, student response data related to discovery learning with Geogebra obtained through student response questionnaires, and data on the ability to understand mathematical concepts obtained through comprehension test of mathematical concepts. The data were analyzed descriptively, both quantitatively and qualitatively, showing that the use of discovery learning with Geogebra was able to fulfill 3 indicators of success in this research, namely learning implementation, student responses to learning, and the ability to understand mathematical concepts themselves